The Diversity and Dynamics of Indigenous Yeast Communities in Grape Must from Vineyards Employing Different Agronomic Practices and their Influence on Wine Fermentation - Bagheri, B.; Bauer, F.F.; Setati, M.E. (South African Journal of Enology and Viticulture, 2016)
The current study evaluated the diversity of yeast species in Cabernet Sauvignon grape must derived from three neighbouring vineyards from a similar terroir but on which significantly different management practices are employed. The fermentation kinetics and yeast population dynamics were monitored from the beginning to the end of spontaneous fermentation. The grape musts were characterised by distinct yeast populations comprising oxidative, weakly fermentative and strongly fermentative yeasts. Different combinations of dominant non-Saccharomyces yeasts were observed in each must, with significantly different assortments of dominant species, including Starmerella bacillaris (synonym Candida zemplinina), Lachancea thermotolerans, Hanseniaspora uvarum, Candida parapsilosis and Wickerhamomyces anomalus. None of these yeast consortia appeared to affect the growth of Saccharomyces cerevisiae or inhibit the overall progress of fermentation. However, the percentage of fermentative yeasts was positively correlated with the fermentation rate. Glucose and fructose consumption rates suggested active participation of both glucophilic and fructophilic yeasts from the onset of fermentation. The data highlight two parameters, viz. initial cell concentration and yeast community composition, as important fermentation drivers and open the possibility to predict fermentation behaviour based on the initial composition of the yeast community.